POTENSI EKOWISATA AIR TERJUN BIBINOI DESA BIBINOI KECAMATAN BACAN TIMUR TENGAH KABUPATEN HALMAHERA SELATAN - Rafly Kurahman; Aqshan Shadikin Nurdin; Nurhikmah Nurhimah; Asiah Salatalohy (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
Ecotourism is a concept that combines the interests of the tourism industry with environmentalists. In South Halmahera district, there are many natural tourist attractions that are still minimally known to the public, one of which is the Bibinoi Waterfall Ecotourism in Bibinoi Village, Bacan District, Middle East, South Halmahera Regency. The purpose of this study is to find out how the potential for ecotourism is and to assess the ecotourism potential of the Bibinoi waterfall in Bibinoi Village, Bacan District, Middle East, South Halmahera Regency. The research method used in this study is the method of observation, interviews, and documentation. The results showed that the tourism object potential of Bibinoi Waterfall based on the object variables of attraction, facilities, accessibility, security had medium potential, while the infrastructure variable of the Bibinoi Waterfall tourism object had low potential. Based on the result of the bibinoi watterfall evalution summary, it is placed in the medium category with a score of 48.